2015
DOI: 10.1371/journal.pone.0125921
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol O-Acyltransferase Type-1 Synthesizes Retinyl Esters in the Retina and Retinal Pigment Epithelium

Abstract: Retinyl esters represent an insoluble storage form of vitamin A and are substrates for the retinoid isomerase (Rpe65) in cells of the retinal pigment epithelium (RPE). The major retinyl-ester synthase in RPE cells is lecithin:retinol acyl-transferase (LRAT). A second palmitoyl coenzyme A-dependent retinyl-ester synthase activity has been observed in RPE homogenates but the protein responsible has not been identified. Here we show that diacylglycerol O-acyltransferase-1 (DGAT1) is expressed in multiple cells of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Although RPE expresses several a t RE synthases, the dominant enzyme is LRAT, which transfers the sn-1 palmitate of lecithin molecules to retinol [ 4 ]. Recent work has suggested that diacylglycerol O-acyltransferase-1 (DGAT1) can also synthesize a t RE in both the retina and RPE by acting as an acyl-CoA: retinol acyltransferase using palmitoyl-CoA as the acyl donor [ 30 ]. Together, LRAT and DGAT1 may exploit the increased FA uptake in hFATP1TG RPE to promote at RE synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although RPE expresses several a t RE synthases, the dominant enzyme is LRAT, which transfers the sn-1 palmitate of lecithin molecules to retinol [ 4 ]. Recent work has suggested that diacylglycerol O-acyltransferase-1 (DGAT1) can also synthesize a t RE in both the retina and RPE by acting as an acyl-CoA: retinol acyltransferase using palmitoyl-CoA as the acyl donor [ 30 ]. Together, LRAT and DGAT1 may exploit the increased FA uptake in hFATP1TG RPE to promote at RE synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…RPE65, an endoplasmic reticulum (ER)‐associated protein , is a key retinoid isomerase in the retinal pigment epithelium (RPE)‐dependent visual cycle that produces 11‐ cis‐ retinal . It catalyzes the synthesis of 11‐ cis ‐retinol from all‐ trans ‐retinyl fatty acid esters, such as all‐ trans ‐retinyl palmitate, synthesized by lecithin:retinol acyltransferase (LRAT) and other enzymes in the RPE . RPE65 is also the isomerase enzyme responsible for the production of meso ‐zeaxanthin, one of the three macular pigments that function as potent antioxidants and light screening pigments to protect macular from blue light damage and reactive oxygen species .…”
mentioning
confidence: 99%
“…The 11-cis-retinol thus formed can be stored as 11-cis-retinyl ester by action of the 11-cis ARAT. For this, two new 11-cis-specific retinyl ester synthases have been identified within the retina: the multifunctional O-acyltransferase (MFAT) (Kaylor et al 2014) and diacylglycerol O-acyltransferase-1 (DGAT1) 8 (Kaylor et al 2015), both found to be present in Müller glial cells and also in the GCL. In another series of studies, it was shown that primary embryonic cultures of Opn4x (+) RGCs were able to take up exogenous all-trans-retinal and isomerize it to 11-cis-retinal and other retinoids such as all-trans-retinol and all-trans-retinyl palmitate (Díaz et al 2017).…”
Section: The Visual Cycle In the Inner Retina And The Contribution Of Rgrmentioning
confidence: 99%